Effects of Normothermic Conditioned Microwave Irradiation on Cultured Cells Using an Irradiation System with Semiconductor Oscillator and Thermo-regulatory Applicator - Asano, Mamiko (Sci Rep, 2017)
We investigated the effects of microwave irradiation under normothermic conditions on cultured cells. For this study, we developed an irradiation system constituted with semiconductor microwave oscillator (2.45 GHz) and thermos-regulatory applicator, which could irradiate microwaves at varied output powers to maintain the temperature of cultured cells at 37 °C. Seven out of eight types of cultured cells were killed by microwave irradiation, where four were not affected by thermal treatment at 42.5 °C. Since the dielectric properties such as ε’, ε” and tanδ showed similar values at 2.45 GHz among cell types and media, the degree of microwave energy absorbed by cells might be almost the same among cell types. Thus, the vulnerability of cells to microwave irradiation might be different among cell types. In HL-60 cells, which were the most sensitive to microwave irradiation, the viability decreased as irradiation time and irradiation output increased; accordingly, the decrease in viability was correlated to an increase in total joule. However, when a high or low amount of joules per minute was supplied, the correlation between cellular viability and total joules became relatively weak. It is hypothesized that kinds of cancer cells are efficiently killed by respective specific output of microwave under normothermic cellular conditions.